Systematic review and meta-analyses on the effects of afternoon napping on cognition. (October 2022) - Leong, Ruth L.F.; Lo, June C.; Chee, Michael W.L.
Abstract: Naps are increasingly considered a means to boost cognitive performance. We quantified the cognitive effects of napping in 60 samples from 54 studies. 52 samples evaluated memory. We first evaluated effect sizes for all tests together, before separately assessing their effects on memory, vigilance, speed of processing and executive function. We next examined whether nap effects were moderated by study features of age, nap length, nap start time, habituality and prior sleep restriction. Naps showed significant benefits for the total aggregate of cognitive tests (Cohen's d = 0.379, CI95 = 0.296–0.462). Significant domain specific effects were present for declarative (Cohen's d = 0.376, CI95 = 0.269–0.482) and procedural memory (Cohen's d = 0.494, CI95 = 0.301–0.686), vigilance (Cohen's d = 0.610, CI95 = 0.291–0.929) and speed of processing (Cohen's d = 0.211, CI95 = 0.052–0.369). There were no significant moderation effects of any of the study features. Nap effects were of comparable magnitude across subgroups of each of the 5 moderators (Q values = 0.009 to 8.572, p values > 0.116). Afternoon naps have a small to medium benefit over multiple cognitive tests. These effects transcend age, nap duration and tentatively, habituality and prior nocturnal sleep.